2023
DOI: 10.1177/14034948221144661
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to COVID-19 vaccine hesitancy in Denmark: A national study in the autumn of 2021

Abstract: Aims: The novelty of the COVID-19 pandemic and fast-developed vaccines may increase concerns about the safety and effectiveness of the COVID-19 vaccine and thereby influence vaccine hesitancy. The aims of this study were to examine (a) the main reasons for COVID-19 vaccine hesitancy and (b) factors associated with COVID-19 vaccine hesitancy. Methods: A nationwide survey was conducted in the autumn of 2021 when most Danes had received at least one dose of a COVID-19 vaccine. The sample ( N=13,570) was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to our findings, women who are hesitant are more likely to be between 40 and 59 years old. Previous European studies do not support this result, since they showed that younger women were more sceptical about the COVID-19 vaccine [14]. These studies also suggested that fake news widely shared on social media played a negative role in highlighting the possible dangers of COVID-19 vaccines on the menstrual cycle, fertility, pregnancy, and breastfeeding [15].…”
Section: Discussionmentioning
confidence: 87%
“…According to our findings, women who are hesitant are more likely to be between 40 and 59 years old. Previous European studies do not support this result, since they showed that younger women were more sceptical about the COVID-19 vaccine [14]. These studies also suggested that fake news widely shared on social media played a negative role in highlighting the possible dangers of COVID-19 vaccines on the menstrual cycle, fertility, pregnancy, and breastfeeding [15].…”
Section: Discussionmentioning
confidence: 87%